China's Evolving Exchange Rate Regime - Das, Sonali (IMF Working Papers; Working Paper, 2019)
China's exchange rate regime has undergone gradual reform since the move away from a fixed exchange rate in 2005. The renminbi has become more flexible over time but is still carefully managed, and depth and liquidity in the onshore FX market is relatively low compared to other countries with de jure floating currencies. Allowing a greater role for market forces within the existing regime, and greater two-way flexibility of the exchange rate, are important steps to build on the progress already made. This should be complemented by further steps to develop the FX market, improve FX risk management, and modernize the monetary policy framework.